MOF modified fabric capable of being used in fields of gas purification and chemical protection and preparation method of MOF modified fabric

Through solvent-free hot pressing method and low temperature calcining technology, the problems of low load fastness and photocatalytic efficiency of photocatalytic textiles are solved, and efficient gas purification and chemical protection performance are achieved, which is suitable for a variety of textile applications.

CN119221287AActive Publication Date: 2024-12-31TIAN JIN GONG YE DA XUE SHAO XING KE QIAO YAN JIU YUAN
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411422224.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2024-12-31
Estimated Expiration
2044-10-12

AI Technical Summary

Technical Problem

Existing photocatalyst textiles have problems such as nanoTiO2 having strong dependence on ultraviolet light, low compatibility with textiles, reduced breathability and moisture permeability, and low MOF load fastness and photocatalytic efficiency, which limits its application in the fields of gas purification and chemical protection.

Method used

The solvent-free hot pressing method is used to organize the metal salt and organic ligand into the fabric, and the interaction between the fiber and the MOF is enhanced by low-temperature calcination, thereby improving the load fastness and photoactivity of the MOF. The specific steps include two-step hot pressing and low-temperature calcination. , ensure stable binding of MOF to fiber and photocatalytic activity.

Benefits of technology

It improves the load fastness and photocatalytic efficiency of MOF on textiles, maintains the breathable and moisture-permeable properties of textiles, and significantly improves the purification capacity and chemical protection performance of gases. It is suitable for household, industrial and military textiles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119221287A_ABST
    Figure CN119221287A_ABST
Patent Text Reader

Abstract

The invention relates to an MOF modified fabric capable of being used for gas purification and chemical protection and a preparation method of the MOF modified fabric. The base cloth in the MOF modified fabric is formed by weaving one or more of cotton cloth, polyester cloth, chinlon cloth, acrylic fiber cloth and aramid fiber cloth in a mixed mode, and MOF is one of Zn-MOF, Zr-MOF or Fe-MOF. The preparation method comprises the following steps: firstly finishing MOF on a base cloth fabric by using a solvent-free hot pressing method, and then calcining the base cloth fabric under certain tension and low-temperature conditions, thereby obtaining the MOF modified fabric with high MOF load fastness and optical activity. The MOF modified fabric has excellent air and moisture permeability, is suitable for the field of gas purification and chemical protection textiles, and compared with the prior art, the MOF modified fabric has the advantage that the loading fastness and photocatalytic activity of MOF on the fabric can be obviously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of functional textiles, and specifically relates to a MOF-modified fabric that can be used in the fields of gas purification and chemical protection, and a preparation method thereof. Background Art

[0002] The rapid development of the textile industry has led to an increasing demand for textiles, and textiles with safety and health functions are more popular. In recent years, photocatalytic textiles obtained by loading photocatalysts on textiles have brought important opportunities for expanding the functional application of textiles. Photocatalyst products can produce highly active species under light, effectively oxidize toxic and harmful gases in the air, kill a variety of bacteria and the toxins they release, thereby achieving functions such as air purification and disinfection, and providing solutions to problems such as air pollution and chemical toxic hazards. According to authoritative reports, 70% of human diseases are related to the indoor environment, among which pollutants such as formaldehyde and benzene VOCs are the culprits of diseases such as pneumonia, leukemia, and cerebral thrombosis. In addition, the rapid development of the chemical industry has spawned more and more chemical varieties, which may leak in the form of gas, steam, etc. during production, storage and transportation, endangering the personal safety of operators; on the other hand, military protective clothing often needs to face attacks such as mustard gas. Photocatalytic textiles can use light energy to convert these chemical agents into non-toxic and harmless small molecules, and therefore have application prospects in curtains, wall coverings, automotive textiles, and military and civilian chemical protective clothing.

[0003] At present, the photocatalytic textiles on the market are mainly nano-TiO 2 It is a photocatalytic component, which is combined with textiles by methods such as chemical fiber masterbatch loading or post-finishing flexible loading. For example, Chinese invention patent application No. CN201510814187.3 discloses a photocatalytic nano-TiO 2 Method for fixing hydrosol on fabric and photocatalyst fabric. However, current photocatalyst textiles still have obvious defects, such as nano-TiO 2 It is highly dependent on ultraviolet light and has low compatibility with textiles, which will significantly reduce the air and moisture permeability of the fabric. At the same time, it has low adsorption and enrichment capacity for low-concentration toxic gases, which limits its photocatalytic efficiency.

[0004] Recently, metal organic framework (MOF) materials, as a crystalline porous compound formed by metal ions or clusters and organic ligands, have attracted much attention in the field of emerging photocatalytic materials due to their rich skeleton structure, large specific surface area, multiple exposed active sites, adjustable band gap structure and easy modification. At present, research on MOF textiles has been reported, but there are still important bottlenecks in its application as photocatalytic textiles. On the one hand, the loading fastness of MOF on textiles is usually poor and not resistant to washing; on the other hand, the homogenized structure of MOF limits its O 2The adsorption and activation of MOFs make their efficiency of photocatalytic production of active species at a low level. By solving these problems, it is expected that new photocatalytic textiles based on MOF components will be developed, which have great application prospects in the fields of gas purification and chemical protection. Summary of the invention

[0005] The purpose of the present invention is to provide a MOF-modified fabric that can be used for gas purification and chemical protection and a preparation method thereof. The fabric uses MOF (Zn-MOF, Zr-MOF or Fe-MOF, etc.) as functional particles and is prepared by a simple two-step method of solvent-free hot pressing and low-temperature calcination. It has the advantages of short process flow, low cost, high MOF loading fastness and high photosensitivity, and has application potential in the fields of clothing, household, industrial and military textiles.

[0006] The technical solution adopted by the present invention is to select a solid precursor of a suitable metal salt and an organic ligand, directly arrange it in the fabric by hot pressing, and then enhance the interaction between the fiber macromolecules and the MOF molecules by low-temperature calcination, and affect the chemical structure and photoactivity of the MOF components. The specific steps are: 1) Cut the base fabric to a certain size, soak it in deionized water for 3 h and wash it repeatedly, and dry it at 40°C for 10 h to remove impurities. Then weigh the base fabric, weigh the metal salt with a mass ratio of 1:10~10:1 to the fabric and the organic ligand powder with a mass ratio of 1:10~10:1, grind it for 5-10 min to fully mix the organic ligand and the metal salt, and evenly apply it on the surface of the base fabric. After wrapping the above composite with thin aluminum foil, hot press it at a hot pressing temperature of 80~150°C and a hot pressing pressure of 1~2 MPa for 5~30 min, wash the obtained fabric repeatedly with DMF and anhydrous ethanol, and dry it at 30~60°C for 2~10 h to obtain MOF pretreated fabric.

[0007] 2) The MOF-pretreated fabric obtained in step 1) is placed in a muffle furnace and calcined for 1 to 180 min under a certain tension (0 to 100 N) and a low temperature of 150 to 250 °C. After being taken out, the fabric is repeatedly washed with DMF, anhydrous ethanol and deionized water, and then dried at 30 to 60 °C for 2 to 10 h to obtain a MOF-modified fabric.

[0008] Preferably, the base fabric used in step 1) is a blend of one or more of cotton, polyester, nylon, acrylic, and aramid, and the base fabric has a gram weight of 10-400 g / m 2 .

[0009] Preferably, the metal salt used in step 1) is one of zinc acetate, zirconium chloride or ferric chloride; and the organic ligand is one of 2-methylimidazole, terephthalic acid or trimesic acid.

[0010] Invention principle and beneficial effects: As a photocatalytic material, MOF has the characteristics of high porosity. After combining it with textiles, it will not affect the air permeability and moisture permeability of textiles. The solvent-free hot pressing method selected by the present invention has the characteristics of short process and wide applicability. Different types of MOF can be grown on base fabrics of various compositions to obtain pretreated fabrics. However, the load fastness of this MOF pretreated fabric is still low, which will cause the MOF to fall off during the cleaning process, and its photocatalytic efficiency is also at a low level due to the low photoactivity of MOF itself. The second step of the present invention is the core step for developing high-performance MOF modified fabrics. The MOF pretreated fabric is placed under tension and low temperature conditions for co-calcination. Its advantages are: the calcination temperature is usually higher than the glass transition temperature of the fiber macromolecules in the fabric, so that the thermoplastic fiber macromolecule chains will be displaced during the calcination process, and new hydrogen bonds and van der Waals forces will be generated between the fiber macromolecules in the new position. Forces, especially after calcination under tension conditions, the fiber orientation degree is improved, the force between the macromolecular chains is enhanced, and the molecular size stability is increased, which is similar to the principle of fabric heat setting. Importantly, MOF molecules also undergo molecular reorganization during the calcination process, and further combine with active or polar groups in fiber macromolecules by coordination, hydrogen bonding, etc., greatly increasing their load fastness on the fabric. On the other hand, due to the action of active / polar groups in fiber macromolecules and the influence of spatial hindrance of fabric, the molecular structure of MOF is easily distorted during the calcination process, resulting in defects, vacancies and unsaturated metal sites, thereby breaking the charge balance of MOF molecular structure and promoting its O 2 The adsorption and activation eventually produces more active oxygen species to improve the gas purification efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1 These are scanning electron microscope (SEM) images of Comparative Examples 1 and 2 and Example 1 of the present invention.

[0012] Figure 2 The air permeability data of Comparative Examples 1 and 2 and Examples 1 and 2 of the present invention are compared.

[0013] Figure 3 The moisture permeability data of Comparative Examples 1 and 2 and Examples 1 and 2 of the present invention are compared.

[0014] Figure 4 The formaldehyde purification data of Comparative Examples 1 and 2 and Examples 1 and 2 of the present invention are compared.

[0015] Figure 5 The purification data of 2-chloroethyl ethyl sulfide of Comparative Examples 1 and 2 and Examples 1 and 2 of the present invention are compared.

[0016] Figure 6 The photocatalytic formaldehyde purification data of Comparative Example 2 and Example 1 of the present invention are compared before and after 5 washings.

[0017] Figure 7 The data are the purification data of formaldehyde under light according to Examples 3, 4, 5 and 6 of the present invention.

[0018] Figure 8 The data are the purification data of 2-chloroethyl ethyl sulfide under light according to Examples 3, 4, 5 and 6 of the present invention.

[0019] Among them: Fabric air permeability is tested according to GB / T 5453-1997; The moisture permeability is tested according to GB / T 12704.1-2009; Formaldehyde purification test conditions: gas phase formaldehyde, initial concentration: 1 mg / L; simulated solar light source: 300W xenon lamp, light intensity 100 mW / cm 2 ; Reaction time 60 min; 2-Chloroethyl Ethyl Sulfide Purification Test Conditions: Liquid 2-Chloroethyl Ethyl Sulfide was dissolved in n-hexane for testing, initial concentration: 2.5 μL / mL; simulated sunlight light source: 300W xenon lamp, light intensity 100 mW / cm 2 ; Reaction time 30 min. DETAILED DESCRIPTION

[0020] The content of the present invention will be further explained below in conjunction with embodiments and drawings, but these embodiments do not limit the protection scope of the present invention. Example

[0021] 1) Select the weight of 100 g / m 2 The polyester fabric was used as the base fabric, cut into 5 cm × 5 cm, soaked in deionized water for 3 h and washed repeatedly, and dried at 40 ° C for 10 h to remove impurities. The weight of the fabric was 0.275 g, and zinc acetate with a mass ratio of 3.9:1 and 2-methylimidazole powder with a mass ratio of 9.7:1 were weighed respectively, ground for 5 min to fully mix the organic ligand and the metal salt, and evenly applied to the surface of the base fabric. After the above-mentioned composite was coated with thin aluminum foil, it was hot-pressed at a hot-pressing temperature of 100 ° C and a hot-pressing pressure of 1.5 MPa for 10 min. The obtained fabric was repeatedly washed with DMF and anhydrous ethanol, and dried at 35 ° C for 5 h to obtain MOF pretreated fabric.

[0022] 2) The MOF-pretreated fabric obtained in step 1) was placed in a muffle furnace and calcined for 30 min under a tension of 10 N and a low temperature of 200°C. After being taken out, the fabric was repeatedly washed with DMF, anhydrous ethanol and deionized water, and then dried at 60°C for 5 h to obtain a MOF-modified fabric.

[0023] The inductively coupled plasma optical emission spectrometer (ICP-OES) technique was used to test the Zn ion content of the fabric after acid hydrolysis, and the MOF content in the fabric was calculated to be 140 mg / g. Example

[0024] The tension in step 2) was adjusted to 0 N, and the rest was the same as in Example 1, to obtain a second MOF-modified fabric. The Zn-MOF content in the fabric was tested and calculated to be 145 mg / g. Example

[0025] The weight is 120 g / m 2 The cotton fabric of the present invention replaces the polyester fabric in Example 1 as the base fabric, and the mass ratio of zinc acetate to fabric in step 1) is adjusted to 3.3:1, the mass ratio of 2-methylimidazole to fabric is adjusted to 8.2:1, and the calcination temperature in step 2) is adjusted to 150°C. The rest is the same as in Example 1, and the third MOF-modified fabric is obtained. The Zn-MOF content in the fabric is 175 mg / g after testing and calculation. Example

[0026] The weight is 100 g / m 2 The polyester-cotton fabric of the present invention replaces the polyester fabric in Example 1 as the base fabric, and the mass ratio of zinc acetate to fabric in step 1) is adjusted to 3.6:1, and the mass ratio of 2-methylimidazole to fabric is adjusted to 9:1, and the rest is the same as Example 1, to obtain a fourth MOF-modified fabric. The Zn-MOF content in the fabric is 151 mg / g after testing and calculation. Example

[0027] The weight is 72 g / m 2 The aramid fabric of the present invention replaces the polyester fabric in Example 1 as the base fabric, and the mass ratio of zinc acetate to fabric in step 1) is adjusted to 5:1, and the mass ratio of 2-methylimidazole to fabric is adjusted to 10:1, and the rest is the same as Example 1, to obtain a fourth MOF-modified fabric. The Zn-MOF content in the fabric is 122 mg / g after testing and calculation. Example

[0028] The metal salt in step 1) of Example 1 was changed from zinc acetate to zirconium chloride, the organic ligand was changed from 2-methylimidazole to terephthalic acid, the mass ratio of zirconium chloride to fabric was adjusted to 3.5:1, the mass ratio of terephthalic acid to fabric was adjusted to 8.8:1, and the rest was the same as Example 1, to obtain the fifth MOF-modified fabric. The Zr-MOF content in the fabric was tested and calculated to be 161 mg / g.

[0029] Comparative Example 1 is a polyester fabric that has been washed with deionized water and dried to remove impurities, and has not been subjected to MOF modification treatment. Comparative Example 2 is a polyester fabric that has been treated in step 1) in Example 1, and has not been treated in step 2).

[0030] Figure 1 It shows that the surface of comparative example 1 is relatively smooth, while a large number of particles appear on the surface of comparative example 2, which proves that MOF particles can be loaded on the surface of the fabric by hot pressing, but their distribution is not very uniform; importantly, the surface MOF structure of embodiment 1 is smooth and evenly distributed, indicating that the heat treatment in step 2) of the present invention can significantly change the existence form of MOF on the fabric surface.

[0031] Figure 2 and Figure 3 It is shown that the air permeability and moisture permeability of the comparative example 1, comparative example 2, embodiment 1 and embodiment 2 are very different, indicating that the treatment of step 1) and step 2) of the present invention will not reduce the air permeability and moisture permeability of the fabric. The moisture permeability of embodiments 1 and 2 is both above 4000 g / (m 2 •24h) or more, fully meeting the requirements of moisture permeable protective clothing.

[0032] Figure 4 It shows that under both dark and photocatalytic conditions, Comparative Example 1 can only remove about 3% of formaldehyde, indicating that the original polyester fabric has only a small adsorption capacity for formaldehyde. The dark adsorption purification rate and photocatalytic purification rate of formaldehyde in Comparative Example 2 reached 23.6% and 52.7%, respectively, indicating that after hot pressing MOF, the adsorption capacity of the fabric for formaldehyde is significantly improved, and it also has a certain ability to photocatalytically degrade and purify formaldehyde. Compared with Comparative Example 2, the adsorption purification rate of formaldehyde in Examples 1 and 2 did not change significantly, but its photocatalytic purification rate was greatly improved, reaching 96.3% and 76.8%, respectively. This shows that the heat treatment in step 2) of the present invention can significantly improve the photocatalytic activity of MOF on the fabric, and applying tension to the fabric during heat treatment can significantly affect its photocatalytic activity.

[0033] Figure 5It is shown that in the purification test of mustard gas simulant 2-chloroethyl ethyl sulfide, the adsorption and photoactivity results of Comparative Example 1, Comparative Example 2, Example 1 and Example 2 are similar to those in the formaldehyde purification test. Comparative Example 2 after hot pressing MOF showed a certain adsorption and photocatalytic purification ability for 2-chloroethyl ethyl sulfide, and Examples 1 and 2 both showed higher photocatalytic purification ability, especially Example 1 obtained by heat treatment under tension conditions, which can achieve a purification rate of 97.5% for 2-chloroethyl ethyl sulfide within 30 minutes, providing conditions for its effective use in chemical protection.

[0034] Figure 6 It shows that after 5 washings, the photocatalytic formaldehyde purification ability of comparative example 2 is significantly reduced, indicating that the MOF after hot pressing is not firmly bonded to the fabric and there is a phenomenon of falling off during the washing process. Importantly, after 5 washings, the photocatalytic formaldehyde purification ability of Example 1 has not changed significantly, and it can still remove nearly 100% of the formaldehyde within 60 minutes. This shows that the MOF in Example 1 described in the present invention has a high bonding strength with the fabric, and the MOF exists stably on the surface of the fabric. This is mainly attributed to the heat treatment in step 2) of the present invention, which can significantly change the existence state of the MOF molecules on the fabric and the interaction between them and the fiber, thereby providing the necessary conditions for its practical application in gas purification or chemical protection.

[0035] Figure 7 and Figure 8 It is shown that Examples 3, 4, 5 and 6 described in the present invention can all be used for the photocatalytic purification of formaldehyde gas or 2-chloroethyl ethyl sulfide, and the removal rates thereof are all above 80%, indicating that the method described in the present invention can be applied to different types of fabric base fabrics and MOF molecules with different structures.

[0036] In summary, the MOF-modified fabric prepared by the present invention has the characteristics of stable combination of MOF and fabric, and shows excellent performance in the fields of gas purification and chemical protection, and has obvious economic benefits in the industrial application of functional textiles.

[0037] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A MOF-modified fabric for gas purification and chemical protection and a preparation method thereof, characterized in that: The MOF-modified fabric is prepared by arranging MOF onto a base fabric by a solvent-free hot pressing method and then calcining the base fabric under a certain tension and low temperature conditions; the preparation method of the MOF-modified fabric comprises the following steps: 1) Cut the base fabric to a certain size, soak it in deionized water for 3 h and wash it repeatedly, and dry it at 40°C for 10 h to remove impurities. Then weigh the base fabric, weigh the metal salt with a mass ratio of 1:10~10:1 to the fabric and the organic ligand powder with a mass ratio of 1:10~10:1, grind it for 5-10 min to fully mix the organic ligand and the metal salt, and evenly apply it on the surface of the base fabric. After wrapping the above composite with thin aluminum foil, hot press it at a hot pressing temperature of 80~150°C and a hot pressing pressure of 1~2MPa for 5~30 min, wash the obtained fabric repeatedly with DMF and anhydrous ethanol, and dry it at 30~60°C for 2~10 h to obtain MOF pretreated fabric. 2) The MOF-pretreated fabric obtained in step 1) is placed in a muffle furnace and calcined for 1 to 180 min under a certain tension (0 to 100 N) and a low temperature of 150 to 250 °C. After being taken out, the fabric is repeatedly washed with DMF, anhydrous ethanol and deionized water, and then dried at 30 to 60 °C for 2 to 10 h to obtain a MOF-modified fabric.

2. The preparation method according to claim 1, characterized in that: The base fabric is preferably a blend of one or more of cotton, polyester, nylon, acrylic, and aramid, with a gram weight of 10-400 g / m 2 .

3. The preparation method according to claim 1, characterized in that: The metal salt is preferably one of zinc acetate, zirconium chloride or ferric chloride; the organic ligand is preferably one of 2-methylimidazole, terephthalic acid or trimesic acid.

Citation Information

Patent Citations

  • Multi-component composite photocatalyst and preparation method and application thereof

    CN106179314A

  • Metal organic framework-zirconium oxide fiber composite material, and preparation method and application thereof

    CN111790355A

  • Preparation method for rapidly growing metal organic framework derivative with assistance of metal salt

    CN113054207A

  • Nanofiber filtering protective material with photocatalytic detoxification function and preparation method thereof

    CN113117418A

  • Ceramic-based composite material for degrading low-concentration formaldehyde and preparation method of ceramic-based composite material

    CN115870006A